STUDY ON DESIGN AND DEVELOP FILE SHARING IN P2P BASED ON NEARNESS - Abhayanand (International Journal of Multidisciplinary Research and Studies, 2020)
specialized for the purpose of serving different computer systems, in P2P interactions the interacting friends usually have skills and duties that are similar to each other. Huh. Traditional network models that can be built on a custodian-server structure are becoming increasingly less common as newer, more advanced networking technologies continue to be developed. It is very difficult to meet customer expectations in typical client/server networks, which is one reason why P2P is becoming increasingly popular among oral exchange networks. More storage, a quicker range of laptop cycles, and increased bandwidth are the primary advantages that P2P has over the client-server version. The number of people using mobile broadband connections is increasing continuously. Additionally, these customers have high expectations for cellular broadband that can be on par with fixed network customers. The fact charges that cell networks are capable of offering at one time affect the types of offerings that can be provided through those networks